Retinal break adjacent to the optic disc causing retinal detachment in a pathological myopia - Noor Aniah A,; Bastion MLC,; Mushawiahti Mustapha, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Retinal detachment is one of the common complications of pathological myopia due to presence of retinal break. However, retinal break commonly occurs in the peripheral retina. This case report illustrates the rare incidence of retinal break adjacent to the optic disc, highlights the possible causes of poor visual outcome following surgical repair as well as the possible measures to treat the complications.